„Tylko pracą mogę zabezpieczyć swoją egzystencję”. Funkcjonariuszki Zakładu Karnego w Fordonie w latach 1945–1956 – rekonesans badawczy - Dąbkowska, Regina (Komunizm: System - Ludzie - Dokumentacja, 2023)
After the Second World War, a prison in Fordon was established for female inmates, both criminal and political. Scholars currently see this institution almost exclusively in the context of the imprisoned “heroes of the Polish underground.” However, that is only partly true as it was also a place of imprisonment for the members of Ukrainian nationalist organizations, German armed formations, and Poles cooperating with the invader during the Second World War. Although some publications on this issue have been released, Fordon prison does not play a major role in any of them. In this article, I would like to introduce the general public to the prison administrative employees, who were mostly women. In my text I present biographical notes of some of them utilizing 124 case files deposited in the Institute of National Remembrance’s archive, which appears to be an authoritative source. My goal was to find an answer to questions such as why women started work in this specific prison and why they decided to quit it